Deteksi Serangan DDOS Pada Jaringan SDN dengan Metode Random Forest - Ekawijana, Ardhian; Bakhrun, Akhmad; Kurniawan, M Teguh (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Distributed Denial Service (DDoS) Attack is an attempt by an attacker to paralyze a network system by flooding it with requests. A busy system can cause a drop in performance and even crash. Software Defined Service (SDN) is a new paradigm in creating a network in a certain area. SDN, with all its advantages and flexibility in implementation, is attractive to implement, but still leaves major security problems, especially being vulnerable to DDoS attacks. This research will detect whether a particular request is DDoS or not. Random Forest is a method for developing Decision Trees to classify whether a request or data packet is an attack or not. Random Forest as a development method from the previous method covers the weakness of overfitting. The results of this research were 98% for accuracy values.